2020
DOI: 10.7326/m20-1738
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator Triage Policies During the COVID-19 Pandemic at U.S. Hospitals Associated With Members of the Association of Bioethics Program Directors

Abstract: for a Task Force of the Association of Bioethics Program Directors* Background: The coronavirus disease 2019 pandemic has or threatens to overwhelm health care systems. Many institutions are developing ventilator triage policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
176
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(183 citation statements)
references
References 14 publications
(17 reference statements)
2
176
0
5
Order By: Relevance
“…Particularly, it has brought to light difficulties with insufficient medical supplies and rationing of resources, precipitating the previously unthinkable: how to triage resources in the case of an absolute deficit. The triage policies proposed by states and hospitals around the country have been nonuniform at best [7]. One common element among these heterogeneous policies is the tendency to further disadvantage the vulnerable populations already affected by COVID-19 (see Table 1 for a list of state policies and their distinguishing features).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, it has brought to light difficulties with insufficient medical supplies and rationing of resources, precipitating the previously unthinkable: how to triage resources in the case of an absolute deficit. The triage policies proposed by states and hospitals around the country have been nonuniform at best [7]. One common element among these heterogeneous policies is the tendency to further disadvantage the vulnerable populations already affected by COVID-19 (see Table 1 for a list of state policies and their distinguishing features).…”
mentioning
confidence: 99%
“…The most widely-commented on form of discrimination has been that of policies that disadvantage the disabled community. A recent study conducted by the Association of Bioethics Program Directors (ABPD) surveying the ventilator triage protocols of hospitals around the country found that 38.5% of hospital protocols factor resource conservation into their protocol criteria, designating that individuals in need of increased clinical attention and resource-use are a lower priority [7]. Only 26.9% of policies specified that allocation decisions should not be based on disability and some of these policies themselves included decision criteria that would disproportionately disqualify the disabled community [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying virulence of this newly emerged coronavirus is particularly severe for older age groups and those with chronic pulmonary and cardiac conditions, diabetes, and other comorbidities. Other factors fueling morbidity and mortality have included limited supplies in personal protective devices and ventilators required for endotracheal intubation (2). With no licensed vaccines available, and antiviral drugs other than Remdesivir (3) showing limited or no efficacy in clinical trials (4)(5)(6)(7), the only methods available to limit infection and disease are public health measures designed to limit human contact and transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely agreed-upon "benefit" to be maximized is survival. [2][3][4][5] One widely adopted protocol developed at the University of Pittsburgh Medical Center (UPMC) addresses expected survival by assigning each patient points for near-term mortality risk (considering major and severe comorbidities) and for acute physiological compromise (utilizing the Sequential Organ Failure Assessment score), with other factors (age, critical worker status) used to modify scores or as tie-breakers. 3 More controversial is whether-or how-quality of life should be considered as a "benefit" to be maximized in triage.…”
mentioning
confidence: 99%